Meat Species Identification by Randomly Amplified Polymorphic DNA - Polymerase Chain Reaction - P. S., Girish.; Sen, A. R.; Vaithiyanathan, S.; Babji, Y.; Rajitha, R.; Muthukumar , M. (Journal of Meat Science, 2011)
Misrepresentation of meat for economic gains is a common economic fraudulence prevalent across the world. In the present study, a molecular technique based on Randomly Amplified Polymorphic DNA Polymerase Chain Reaction (RAPD - PCR) was tried for differentiation of meat of cattle (Bos indicus), buffalo (Bubalus bubalis), sheep (Ovis aries), goat (Capra hircus) and chicken (Gallus gallus). RAPD profile of cattle revealed four amplicons of size 148, 234, 363 & 452 bp, whereas, that of buffalo revealed amplicons of size 148, 273, 345 & 429 bp. Whereas, sheep and goat yielded three (147, 645 & 389 bp) and four amplicons (145, 375, 613 & 777 bp), respectively. Chicken RAPD profile indicated four amplicons of size 263, 351, 467 & 689 bp. Results indicated that, RAPD PCR can be of use in differentiation of meat from different meat animals which can be employed for authentication of meat and prevention of misrepresentation of meat.
Keywords: Meat; adulteration; DNA; PCR; RAPD